2011
DOI: 10.1590/s0034-737x2011000600010
|View full text |Cite
|
Sign up to set email alerts
|

Composição da entomofauna da Floresta Nacional do Araripe em diferentes vegetações e estações do ano

Abstract: Composition of entomofauna on the Araripe National Forest in different vegetation types and year seasonsThe occurrence of insects has great ecological significance and is related to environmental factors, food availability, and refuge. We assess the composition of the entomofauna in different vegetation types (cerrado, carrasco and humid forest), and seasons in the Araripe National Forest, Crato-CE, by weekly collections made in the dry season (September to December) and in the rainy season (April to July), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 22 publications
1
12
0
15
Order By: Relevance
“…The first one, especially in the pasture area, and the second one more frequent in the preserved area. Dung beetles are sensitive to changes in habitat, since they have low dispersal ability, specialized diet, based mainly on mammalian excreta, and display distribution strongly influenced by vegetation cover (Halter and Arellano, 2002, Costa et al, 2009, Azevedo et al, 2011. This explains the larger amount of the insects collected in the preserved area.…”
Section: Discussionmentioning
confidence: 99%
“…The first one, especially in the pasture area, and the second one more frequent in the preserved area. Dung beetles are sensitive to changes in habitat, since they have low dispersal ability, specialized diet, based mainly on mammalian excreta, and display distribution strongly influenced by vegetation cover (Halter and Arellano, 2002, Costa et al, 2009, Azevedo et al, 2011. This explains the larger amount of the insects collected in the preserved area.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of the order Diptera was not only influenced by temperature but also by precipitation. Azevedo et al (2011) stated that each insect group responds differently to annual climatic variations. The authors observed that frugivorous, phytophagous and detritivorous beetles and the Gryllidae family of the order Orthoptera were more abundant in the dry season, whereas the frugivorous and scavenging Diptera predominated in the rainy season, suggesting that temperature and precipitation may influence the availability of food and shelter for these orders.…”
Section: Arthropod Bioindicators Of Environmental Qualitymentioning
confidence: 99%
“…According to Queiroz et al (2006), ants are excellent biological indicators, promoting soil fertility improvement and acting as efficient biological control agents. For Azevedo et al (2011), large ant presence in almost all ecosystems is justified through ant cosmopolitan habits, ease of adaptation and generalist eating habits. According to Braga et al (2010), ants are good indicators of impact on ecosystems, as they are often present in various ecosystems and are very sensitive to disturbance.…”
Section: Resultsmentioning
confidence: 99%
“…Insect presence in an area is due to food availability and vegetation, among other factors (Azevedo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%